Decreased Activity of the Na + /H + Exchanger by Phosphodiesterase 5A Inhibition Is Attributed to an Increase in Protein Phosphatase Activity - Yeves, Alejandra del Milagro (2010)
The beneficial effect of phosphodiesterase 5A inhibition in ischemia/reperfusion injury and cardiac hypertrophy is well established. Inhibition of the cardiac Na+/H+ exchanger (NHE-1) exerts beneficial effects on these same conditions, and a possible link between these therapeutic strategies was suggested. Experiments were performed in isolated cat cardiomyocytes to gain insight into the intracellular pathway involved in the reduction of NHE-1 activity by phosphodiesterase 5A inhibition. NHE-1 activity was assessed by the rate of intracellular pH recovery from a sustained acidic load in the absence of bicarbonate. Phosphodiesterase 5A inhibition with sildenafil (1 μmol/L) did not affect basal intracellular pH; yet, it did decrease proton efflux (JH; in millimoles per liter per minute) after the acidic load (proton efflux: 6.97±0.43 in control versus 3.31±0.58 with sildenafil; P<0.05). The blockade of both protein phosphatase 1 and 2A with 100 nmol/L of okadaic acid reverted the sildenafil effect (proton efflux: 6.77±0.82). In contrast, selective inhibition of protein phosphatase 2A (1 nmol/L of okadaic acid or 100 μmol/L of endothall) did not (3.86±1.0 and 2.61±1.2), suggesting that only protein phosphatase 1 was involved in sildenafil-induced NHE-1 inhibition. Moreover, sildenafil prevented the acidosis-induced increase in NHE-1 phosphorylation without affecting activation of the extracellular signal–regulated kinase 1/2-p90RSK pathway. Our results suggest that phosphodiesterase 5A inhibition decreases NHE-1 activity, during intracellular pH recovery after an acidic load, by a protein phosphatase 1–dependent reduction in NHE-1 phosphorylation.